Adopsi Internet Of Things (IOT) Pada Rantai Pasok Pangan Guna Mengurangi Food Lost Waste (FLW) Rantai Pasok Pangan - Mutia Perwita Sari; Shofwatunnida Septarini (Jurnal Nasional Teknologi dan Sistem Informasi, 2025)
Soybeans are one of the largest food commodities in Indonesia. Tempe is a soybean product that is a daily staple in Indonesian cuisine. Tempe is a traditional food with high nutritional value, and it is consumed by almost all ages. A common problem is that tempeh doesn't last long after being purchased at the market. Poor quality tempeh affects its taste when consumed. Poor quality tempeh is usually caused by unpredictable weather during the fermentation process and a short storage period. This can increase food loss and waste (FLW). FLW itself is the loss and waste of food, making FLW monitoring crucial for improving food security and mitigating climate change. By measuring and monitoring temperature and humidity parameters in real time, the system integrates IoT technology, such as the DHT11 sensor, to measure temperature and humidity, ensuring that the tempe fermentation process is maintained at a stable temperature and runs optimally.Furthermore, because it is IoT-based, the temperature on this device can be monitored in real time via a smartphone, provided it is connected to the internet. In the monitoring application there is an interface that displays the temperature and humidity at that time and there is a bottom for turning the lights and fans on or off manually.